2004
DOI: 10.1086/422207
|View full text |Cite
|
Sign up to set email alerts
|

Subaru Deep Survey. V. A Census of Lyman Break Galaxies atz ≃ 4 and 5 in the Subaru Deep Fields: Photometric Properties

Abstract: We investigate photometric properties of Lyman Break Galaxies (LBGs) at z = 3.5 − 5.2 based on large samples of 2,600 LBGs detected in deep (i ′ 27) and wide-field (1,200 arcmin 2 ) images taken in the Subaru Deep Field (SDF) and the Subaru/XMM Deep Field (SXDF) using broad band B, V , R, i ′ , and z ′ filters. The selection criteria for the LBG samples are examined with 85 spectroscopically identified objects, and the completeness and contamination of the samples are estimated from Monte Carlo simulations bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
492
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 416 publications
(534 citation statements)
references
References 94 publications
37
492
4
1
Order By: Relevance
“…Both of them agree with the R − i colours of our SXDS control sample within the errors. We then extracted 11 sources with i < 26.0 from our sample (R − i colours of 0.08 ± 0.4), and found that 10 of them satisfy the LBG selection criteria by Ouchi et al (2004). The remaining one source has slightly red R − i colour, but fainter than 1σ level in B band, which is consistent with the Lyman-break feature.…”
Section: The Tnj1338 Field Samplementioning
confidence: 74%
See 1 more Smart Citation
“…Both of them agree with the R − i colours of our SXDS control sample within the errors. We then extracted 11 sources with i < 26.0 from our sample (R − i colours of 0.08 ± 0.4), and found that 10 of them satisfy the LBG selection criteria by Ouchi et al (2004). The remaining one source has slightly red R − i colour, but fainter than 1σ level in B band, which is consistent with the Lyman-break feature.…”
Section: The Tnj1338 Field Samplementioning
confidence: 74%
“…The raw data were reduced with SDFRED20080620 (Yagi et al 2002;Ouchi et al 2004) and IRAF. We flat-fielded using the median sky image after masking sources.…”
Section: Subaru Imaging Datamentioning
confidence: 99%
“…In brief, data were obtained mostly under photometric conditions with average seeing of 0 9-1 0 for all five narrowband and two intermediate-band filters. These data were reduced following standard reduction procedures using SDFRED (Yagi et al 2002;Ouchi et al 2004), a software package designed especially for Suprime-Cam data.…”
Section: The Subaru Deep Fieldmentioning
confidence: 99%
“…To achieve this goal, a set of continuum-selected objects brighter than z + < 25 or IRAC [4.5 μm] < 23.5 were selected to satisfy the above magnitude and mass limits, respectively. From this flux-limited sample, B J , g + , V J , r + , i + , and z + LBGs were selected using known criteria (Ouchi et al 2004;Capak et al 2004Capak et al , 2011aIwata et al 2003;Hildebrandt et al 2009). Objects with a probability greater than 50% of being at z > 4, based on the Ilbert et al (2010) photo-z catalog, were also included if they met the flux limit.…”
Section: Source Selectionmentioning
confidence: 99%
“…The study of the high-redshift universe and the early evolution of galaxies has primarily relied on two techniques to obtain large samples of high-redshift galaxies, the Lyman break technique (LBGs; Steidel et al 1999;Ouchi et al 2004;Bouwens & Illingworth 2006, and references therein) and narrowband surveys targeting Lyα emitting galaxies (LAEs; Hu & McMahon 1996;Rhoads & Malhotra 2001;Ajiki et al 2003;Hu et al 2004Hu et al , 2010Taniguchi et al 2005;Murayama et al 2007;Gronwall et al 2007;Ouchi et al 2008, and references therein). Studying the difference in the nature and properties of the two populations, selected by these two techniques, helps to understand early stages of galaxy formation and provides constraints on reionization.…”
Section: Introductionmentioning
confidence: 99%